Analysis of Microbial Community Structure and Denitrification Mechanism by Functional Bacteria in HMBR System - LI Ying; SHI Haochen; LIU Qiang; ZHENG Xiaoying; ZHENG Jiaxiong; XIANG Wei; QU Jixiang (Renmin Zhujiang)
This paper operates a hybrid membrane bioreactors (HMBR) under the conditions of 30 days of sludge retention time (SRT) and 10 hours of hydraulic retention time (HRT), collects the activated sludge samples in the membrane filament surface, filler surface and mixed liquid and detects & analyzes the microbial community structures of activated sludge in the three positions through high-throughput sequencing, discusses the community structures and the difference of denitrifying bacteria of the three samples, and analyzes the denitrification mechanism of HMBR from the perspective of microorganism function. The results show that the dominant group in the HMBR system is Proteobacteria, accounting for 62.18% of the total clones. Anaerolineaceae, Flavobacterium, Nitrosomonas, and Nitrospira which belong to Bacteroidetes in the suspension filler and mixed liquid play a key role in enhancing denitrification.